TrexAB, a novel tetracycline resistance determinant in Streptococcus dysgalactiae - Glambek, Marte; Kjos, Morten; Mårli, Marita T.; Salehian, Zhian; Skrede, Steinar; Sivertsen, Audun; Kittang, Bård R.; Oppegaard, Oddvar (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundStreptococcus dysgalactiae (SD) is a potent pathogen associated with infections in a broad range of host species. Notably, a substantial proportion of SD isolates exhibit reduced susceptibility to tetracycline but lack identifiable resistance determinants. In the present study, we wanted to explore the genetic basis for this low-grade resistance to tetracycline.MethodsGenome-wide association studies were performed on a collection of 407 SD genomes to identify potential novel resistance determinants. Two strains of SD, belonging to each of the subspecies dysgalactiae and equisimilis were used for mutagenesis. Natural transformation was exploited to knock out resistance gene candidates, and the resultant mutants were compared with their respective wildtypes regarding susceptibility to tetracycline, doxycycline, minocycline, tigecycline, erythromycin, gentamicin, clindamycin and ciprofloxacin.ResultsWe identified a two gene operon, herein designated trexAB, significantly associated with reduced susceptibility to tetracycline. The proteins encoded by the operon were predicted in silico to constitute a heterodimeric efflux transporter. The knockout of trexAB led to a 16- to 32-fold reduction in minimum inhibitory concentration (MIC) for tetracycline and a 4-fold reduction in MIC for tigecycline in the investigated strains. No differences between mutants and wildtypes were observed for other antibiotics included in the test panel. Whole genome alignment of mutants and their respective wildtypes revealed no differences other than the expected differences caused by the knockout.ConclusionWe have characterized a novel operon causing low-grade resistance to tetracycline in SD. The MIC distribution of trexAB-positive isolates is intersected by the current EUCAST susceptibility breakpoint, and our findings are relevant for future revisions and determinations of adequate breakpoints for tetracycline in S. dysgalactiae.